Internalizing Maja Labo Dahu Values to Strengthen Students’ Ethical Use of Mobile Phones at SMAN 1 Bima City - Yudi Ananto; Ridwan; Asfari; Juwaidin (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the internalization of Maja Labo Dahu values as an effort to strengthen students’ ethics in using mobile phones at SMAN 1 Bima City. Theoretical framework: This study is grounded in character education theory, local wisdom theory, and digital ethics theory. Literature review: Previous studies highlight the importance of integrating local cultural values into character education to address moral challenges arising from technological advancement. Method: This study employed a descriptive quantitative approach involving 83 students from grades X and XI at SMAN 1 Bima City. Data were collected through a questionnaire consisting of 55 statements covering students’ understanding of Maja Labo Dahu values, ethics in mobile phone use, the utilization of mobile phones for learning, discipline in mobile phone use, and behavior on social media. The collected data were analyzed using descriptive statistical techniques to determine the level of students’ ethical behavior and the extent of value internalization. Results: The findings reveal that the overall average score was 3.76, categorized as good. Students demonstrated a high level of understanding of digital ethics (4.55), awareness of positive mobile phone use (4.55), utilization of mobile phones as learning resources (4.54), compliance with school regulations (4.41), and self-control in mobile phone use (4.08). In contrast, negative behaviors related to mobile phone use, including online gambling, cyberbullying, accessing inappropriate content, playing games during lessons, and cheating through mobile phones, were found to be in the low category (1.07–2.47). These findings indicate that the values of Maja and Dahu serve as effective moral controls that encourage students to use mobile phones responsibly, ethically, and in accordance with social and religious norms. Implications: The study emphasizes the importance of integrating local wisdom into character education programs as a strategy to foster ethical digital behavior among students. Schools can utilize Maja Labo Dahu values as a cultural and moral foundation for promoting responsible technology use and preventing digital misconduct. Novelty: The novelty of this study lies in demonstrating how the internalization of Maja Labo Dahu values strengthens students’ digital ethics in mobile phone use, offering a local wisdom-based character education model for the digital era.